Wordsworth and the Passions of Critical Poetics - Allen, S. author. aut Link
XXIII, 191 p.
Keywords: This scholarly study presents a new political Wordsworth: an artist interested in 'autonomous' poetry's redistribution of affect. No slave of Whig ideology, Wordsworth explores emotion for its generation of human experience and meaning. He renders poetry a critical instrument that, through acute feeling, can evaluate public and private life.